(untitled) (Research, Society and Development, 2021)
Endentulism is a health problem in Brazil, as it affects the patient generating psychological, social and functional problems. Treatments with implant supported prostheses must be very well planned and executed, to have an adequate maintenance and longevity. Thus, the present study reports a clinical case of replacement of a lower implant-supported prothesis in accordance with the traditional Branemark protocol by an overdenture, considering the patient’s biopsychosocial principles. A 92-year-old female patient attended an Overdenture extension project for total toothless in geriatrics at the Escola Técnica de Saúde (ESTES-UFU), complaining of halitosis, difficulty in cleaning the implant supported prostheses and general discomfort with the prostheses. The intraoral clinical examination revealed the presence of a superior mucosal prosthesis and a implant supported prostheses in the mandibule, which presented inadequate occlusal stability, high degree of wear of the resin teeth and the presence of biofilm, revealing an inability of the patient to perform the correct cleaning, given the loss of motor coordination by the patient’s age. The treatment plan was defined by the adequacy of the oral environment, brushing orientation and later the manufacture of two new prostheses. A conventional upper prosthesis and a lower overdenture prosthesis over Equator abutments were made, taking advantage of the 4 implants in an adequate position. After installing the prostheses, it was possible to diagnose greater chewing comfort and an improvement in hygiene. Thus, it was possible to promote quality and longevity in the treatment according to the patient’s need and age, restoring oral health and self-esteem.